Comparison of measured and calculated concentrations of air pollution from engines at the airport - Запорожець, О.І.; Синило, К.В. (Proceedings of National Aviation University, 2009)
Experimental measuring of air pollution in airport, produced by aircraft emission, is described and compared with calculated values due to modeling software PolEmiCa.